Introduction to programming with Java a problem solving approach - Dean, John 1962-; Dean, Ray 1936- (Mc-Graw-Hill LLC, 2021)
"This book is of computer programming. This edition includes new chapters, reorganized chapter sections, new programming constructs, new program examples, and all new exercises and lots of problem-solving practice."--Provided by publisher.